De la catégorie du genre en Cris - Vaillancourt, Louis-Philippe (Anthropologica, 2022)
The Cree language recognizes two genders which are usually referred to as animate/inanimate. This article explores the meaning of this distinction which cannot be reduced to living/non-living.